Effectiveness of Some Concentrations of Rambutan Wood Liquid Smoke to Inhibit The Growth of Cercospora sp. Secara in Vitro - Mahmud, Yusmar; Nuriman, Fiqi; Septirosya, Tiara (Jurnal Multidisiplin Indonesia, 2024)
Cercospora sp. is a fungus that causes leaf spot disease in oil palm plants, potentially affecting productivity and harming oil palm cultivation. Long-term use of synthetic fungicides can lead to resistance, resurgence, and leave harmful residues in the environment. As an alternative solution, the utilization of liquid smoke from rambutan wood offers a cost-effective, environmentally friendly, and antifungal option to inhibit the growth of leaf spot disease. This study aims to determine the effective concentration of rambutan wood liquid smoke in inhibiting the growth of Cercospora sp. Vitro. The research was conducted from December to March 2024 at the Laboratory of Pathology, Entomology, Microbiology, and Soil Science, Faculty of Agriculture and Animal Husbandry, Sultan Syarif Kasim State Islamic University Riau. The experimental method used was a completely randomized design with six treatments (0%, 1%, 2%, 3%, 4%, and 5%), each repeated four times, resulting in 24 experimental units. Observed parameters included total phenol content analysis of liquid smoke, macroscopic observations, growth rate (cm/day), and inhibition rate (%) of Cercospora sp. The results showed a total phenol content of 1.76%. Liquid smoke from rambutan wood at a concentration of 2% was highly effective in inhibiting the growth of Cercospora sp., completely stopping the growth rate to 0 cm/day and categorizing it as a highly effective fungicide with an effectiveness percentage of 100%.